Promoting Multi-Actor ‘Innovation’ Platforms for Agribusiness Value Chain Models in Great Lakes Region of East Africa - Nyamai , D. O.; Ouma , G. O; J. , Osida (African Journal of Education,Science and Technology (AJEST), 2017)
The paper emphasizes the application of appropriate ICT tools to upgrade the smallholder producers in agricultural sector and to facilitate commercially-oriented production. In this context, the study examines digitalization of agribusiness value chains as a key ingredient in the industrialization process of the region which depends largely on smallholder agriculture. This is even more so considering the fact that many parts of the region still lack basic infrastructure such as ICT to spur industrialization of the sector by upgrading the agricultural sector and to facilitate market-oriented production. The study’s findings as well as in a number of baseline surveys in the region, notably, Green Forest Social Investment (GFSI, 2014) show that limited access to basic digital infrastructure such as ICT is major impediment in agricultural transformation from production of agricultural raw materials to processing and market driven agriculture. Furthermore, analysis of agribusiness opportunities, key drivers and challenges, including production conditions, marketing, and institutional support overwhelmingly call for the need to digitally connect agribusiness value chain players together. Also, the study has established that removing principal constraints associated with linkages and networking will enhance competitiveness of agribusiness in global agriculture by the region which incidentally fall within the armpit of effective information management based on production-to-market systems continuum. In developing a digitized value chain, the paper has considered the perspective of smallholder farmers and groups (who are only partially farming for the market) by taking into account the ways they need support in the short to medium-term. Equally critical is the recognition that such support must be self-sustaining and the value chain actors (producers/smallholders, service providers, input suppliers, agricultural processors and marketers, among others) need to be able to manage things for themselves. Key to this approach is the “knowledge of opportunities” concept. In this consideration, it was noted that different agribusiness value chain actors/stakeholders provided information on the various opportunities that they are involved in that exist to support agribusiness and rural development but these are rarely available widely to all the value chain actors. For instance, the study also established that majority of value chain actors are still least informed about access to capital. This is a huge deterrent to agribusiness and yet there are plenty of opportunities for access to such resources. These gaps explains the study’s motivation for digital intervention to upscale uptake of popular agribusiness value chains such as the sunflower model, in which participating value chain actors are digitally networked in an agribusiness framework.